COVID-19 Testing Experience in a Resource-Limited Setting: The Use of Existing Facilities in Public Health Emergency Management - Assefa, Nega; Hassen, Jemal Yousuf; Admassu, Desalegn; Brhane, Mussie; Deressa, Mersen; Marami, Dadi; Teklemariam, Zelalem; Dessie, Yadeta; Oundo, Joseph (Frontiers in Public Health, 2021)
Introduction: COVID-19 is a public health emergency with little testing and treatment experiences at its occurrence. Diagnostic and treatment rapidly changed in the world including Ethiopia. Haramaya University has strived to change its diagnostic capacity using its existing facilities in response to the national call. Objective: This summary aims to detail experiences of setting up COVID-19 testing in Haramaya University laboratories. Approach: Desktop exercise has been conducted to understand the startup and implementations of COVID-19 testing in the two laboratories located in Haramaya University, Hararghe Health Research Partnerships (HHR) and CAGED laboratories. Communication, formats, guidelines and standards were skimmed and summarized. Discussion with those involved in the start-up and implementation of the testing has been made. Ideas were summarized to learn the experiences the COVID-19 testing exercises Lesson learnt: This is a huge experience for Haramaya University to participate in the national call to increase the testing platform in the management of COVID19. Close work relationship with the public health executives at all levels showed university’s commitment to public service. The University has used the opportunity to advance its molecular testing capability by training its staff and students. The University has also contributed to the capacity development for laboratories in the surrounding areas including Harar, Somali, Oromia and Dire Dawa. The Phenomenon was an opportunity in harnessing existing resource for the benefit of the public during in such dire needs to save lives.